Quality Control of Tanzanian Curcuma longa L. Rhizome: An Anti-Inflammatory Drug (Tanzania Medical Journal, 2007)
Background: People in developing countries have been using medicinal plants for their health care for a long time. Most of the plants they use have been officially recognized in many Pharmacopoeias world wide. Medicinal plants have also provided templates that have lead to discovery of currently clinically useful drugs. C. longa L. is clinically recommended for the treatment of hyper acidity, flatulent or atonic dyspepsia, peptic ulcers and inflammation due to rheumatoid arthritis.Broad objective: To do a quality control on the medicinal plant Curcuma longa L. growing in Tanzania according to WHO specifications. Study settings: School of Pharmacy, MUCHS, Dar-es-Salaam, Tanzania.Methodology: C. longa rhizomes collected from Tanga were purchased at Kisutu market. WHO set standards for widely used medicinal plants, were used. The macroscopic and microscopic characters of the rhizome were recorded. Powdered plant material were then extracted in methanol and the extract used for carrying out other identity tests including thin layer chromatography and high performance liquid chromatography, curcumin as a standard. Quality tests like total ash, acid insoluble, water and alcohol soluble extractives, curcumin and volatile oil contents, were determined according to WHO monographs.Results: As the amount of active ingredients can differ in plants of the same species growing in different climates, soil and time of collection, quality control results on C. longa rhizome growing in Tanzania show that it meets the WHO set standards. The results of this study, when compared with specifications set by WHO, (in brackets), for C. longa rhizome show that the amount of total ash is 6.8 (not more than 8%), acid insoluble ash 0.98% (not more than 1%), water soluble extractive 13.2 % (not less than 9%), alcohol soluble extractive 17% (not less than 10%), percentage volatile oil 5.4% (not less than 4%) and curcuminoids 7.1% (not less than 5%). Conclusion and Recommendations: C. longa growing in Tanzania meets WHO quality specifications as a medicinal plant. It can therefore be used as a raw material in the manufacture of different drug formulations. The rhizome can be used in powder form, extract or the volatile oil obtained from it.Tanzania Medical Journal Vol. 22 (1) 2007: pp. 20-26